PERAN BHABINKAMTIBMAS DALAM MENCEGAH TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN DI WILAYAH HUKUM POLRES PURWAKARTA - Adhi Utomo (Advances in Police Science Research Journal, 2020)
The background of this research is the high level of theft by weighting crime in the region of Purwakarta. One of the prevention efforts from Indonesian National Police on taking action of this condition is through Bhabinkamtibmas. The purpose of this thesis is to (1) identificate the role of Bhabinkamtibmas in preventing theft by weighting (2) identificate factors that effect the role of Bhabinkamtibmas in preventing theft by weighting. This thesis use 2 theories which consist of communication theory and management theory. Author use four concept which consist of role concept, crime prevention concept, bhabinkamtibmas concept and theft by weighting concept. This research use qualitative approach with analysis descriptive method. The type of research is field research which focuses on the location which is Purwakarta. The technique to collect data is to by doing interviews and observation. The source of data comes from primary source and secondary source. The result from this research is that theft by weighting in Purwarakta is fluctuative with many kinds of modus. Bhabinkamtibmas have the role to prevent and the factor that effects in preventing theft by weighting. The conclusion of this research is that based on the discovery of this research, there’s a lack of personnel of Bhabinkamtibmas in giving counseling, also there’s a lot of personnel that haven’t take courses or education, lack of quality of the personnel, lack of equipment. Factor of the relationship between Bhabinkamtibmas and the society to maintain public safety so the society have synergy with Bhabinkamtibmas in keeping public safey to prevent theft by weighting. The suggestion that the author can give is to enhance the capability of the personnel by taking courses, resolving the lack of personnel in Unit Binmas, fixing the system of human resources, fulfilling equipment especially transportation, giving materials that’s updated to the current condition of the society by using social media.